Pharmacokinetic Behavior of Vincristine and Safety Following Intravenous Administration of Vincristine Sulfate Liposome Injection in Chinese Patients With Malignant Lymphoma - Yang, Fen; Jiang, Min; Lu, Ming; Hu, Pei; Wang, Hongyun; Jiang, Ji (Frontiers in Pharmacology, 2018)
Objective: This phase Ia study was designed to assess the pharmacokinetic (PK) characters of free vincristine (F-VCR, refer to as nonliposomal VCR and VCR released from lipsome) and total vincristine (T-VCR, the sum of both liposomal VCR and F-VCR), urinary excretion and safety of intravenous administration of vincristine sulfate liposomes injection (VSLI) in Chinese patients with malignant lymphoma and compare the results with those for conventional vincristine sulfate injection (VSI). Methods: In the phase Ia, randomized, open-label, two sequence cross-over study, patients from one group were exposed to treatment 1 including Cytoxan (cyclophosphamide power injection), Hydroxyrubicin (adriamycin power injection), Oncovin (VSI) and Prednisone tablets (standard CHOP scheme) before crossed over to treatment 2 (modified CHOP scheme in which VSI was replaced with VSLI). Patients from another group received treatments in reverse order. Results: In this phase Ia study, a total of eight subjects participated. VCR elimination from the circulation after injection of VSLI was characterized by a significantly increased maximum concentration (Cmax, 86.6 ng/mL) and plasma area under the plasma concentration-time curve from zero to infinity (AUC0-Inf, 222.1 ng/mL•h), markedly decreased distribution volume (Vz, 224.1 L) and plasma clearance (CL, 8.9 L/h) compared to lower Cmax (26.6 ng/mL) and AUC0-Inf (95.1 ng/mL•h), larger Vz (688.8 L) and CL (22.1 L/h) for VSI. The small proportion of F-VCR following infusion of VSLI in circulation was reflected by very low Cmax (1.8 ng/mL) and AUC0-Inf (50.5 ng/mL•h). Less than 3% of the administered dose of VSLI was excreted in urine and the extent was similar to that for VSI. The elimination percentage of 40%-21%-14% for VSI changed to 6.2%-24%-39% for VSLI at intervals of 0-5h, 5-13h and 13-25h, respectively. Significant difference of toxicity between VSLI and VSI was not observed. Conclusion: VSLI exhibits higher AUC0-Inf of T-VCR, lower CL and Vz compared with VSI. VSLI was well tolerated, maybe due to the markedly decreasing AUC0-Inf of F-VCR. The majority of VCR was enveloped in liposome and VCR was released gradually from liposome following injection of VSLI. Liposomal encapsulation of VCR does not alter the route and extent of VCR excretion in urine.